Election administration in Nigeria: A factor leading to declining voter turnout - Akanmu, Temitope Olukunmi; Adanlawo, Eyitayo Francis (International Journal of Innovative Research and Scientific Studies, 2025)
This paper discusses the complex relationship between election administration and voter turnout in Nigeria. By identifying and analysing the election administrative factors contributing to low voter turnout, this study delves into the areas where the administration of election processes and procedures serves as a significant causal factor. The analysis draws on relevant scholarly and policy literature to map out emerging trends, structural challenges related to election administration and voter turnout. The analysis reveals that the causes of low voter turnout in Nigeria are not limited to electoral violence, but it also includes maladministration or administrative failures of the electoral processes and procedures by INEC. The paper proposed several recommendations for administering elections to enhance voter turnout as a strategy for future elections in Nigeria. This paper offers a comprehensive understanding of the electoral administrative procedures that pose challenges to the electoral process and deter Nigerian voters from participating in elections.